Survey on Implementation of Early Literacy Interventions by Parents of Deaf Children - Yulvia Sani; Ossy Firstanti Wardany; Heni Herlina (Department of Special Education, 2022)
This study aims to determine whether parents of deaf children in Lampung conduct early literacy interventions. This research used a survey type quantitative method. The research subjects were 6 parents of deaf children aged 4-8 years. It collected data using a questionnaire distributed via Google Form to parents of deaf children. The study results found that 83 percent did early literacy intervention at home. Parents' activities to carry out early literacy intervention are reading aloud, natural intervention, using video, and making DIY media. All parents did the planning. The planning and implementation of early literacy intervention activities carried out by parents encountered various obstacles. Most of the solutions chosen were discussed with experts/therapists/ teachers. So it can be said that most parents of deaf children in Lampung Province carry out early literacy interventions planned and carried out through collaboration with families and expert assistance.